Smart Manufacturing and Industry 4.0 - Ahmad Barari; Marcos Sales Guerra Tsuzuki (Applied Sciences, 2023)
Smart manufacturing processes and systems have received great attention through the latest innovations, ongoing efforts, and best practices in the Industry 4 [...]